2020
DOI: 10.1136/bmjopen-2020-040683
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of electronic cigarette use among Swedish teenagers: a population-based cohort study

Abstract: ObjectivesThe aim was to identify predictors of electronic cigarette (e-cigarette) use among teenagers.Design and settingA prospective population-based cohort study of schoolchildren in northern Sweden.ParticipantsIn 2006, a cohort study about asthma and allergic diseases among schoolchildren started within the Obstructive Lung Disease in Northern Sweden studies. The study sample (n=2185) was recruited at age 7–8 years, and participated in questionnaire surveys at age 14–15 and 19 years. The questionnaire incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 46 publications
2
11
0
2
Order By: Relevance
“…Twenty-five observational studies involving 966,376 participants, three case studies, one opinion article, eight reviews, and four systematic reviews with three meta-analyses were identified for this query ( Table 3 ). Several researchers have pointed out that EC might lead previously “nicotine naïve youths” to tobacco cigarette use [ 18 , 62 , 63 , 64 , 114 ]. Tobacco cigarette use and asthma were found to be associated with lifetime EC use and young adults who used ECs persisted with smoking tobacco cigarettes [ 84 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Twenty-five observational studies involving 966,376 participants, three case studies, one opinion article, eight reviews, and four systematic reviews with three meta-analyses were identified for this query ( Table 3 ). Several researchers have pointed out that EC might lead previously “nicotine naïve youths” to tobacco cigarette use [ 18 , 62 , 63 , 64 , 114 ]. Tobacco cigarette use and asthma were found to be associated with lifetime EC use and young adults who used ECs persisted with smoking tobacco cigarettes [ 84 ].…”
Section: Resultsmentioning
confidence: 99%
“…It has been pointed out that ECs could serve as a gateway to tobacco cigarette smoking or illicit drugs (the “gateway effect”) [ 19 , 63 ]. One cohort study and two large cross-sectional studies—including more than 670,000 participants, with many asthmatics among them—have demonstrated the association between EC and tobacco smoking, snus, alcohol, and other substance use [ 68 , 75 , 114 ]. EC devices can contain cannabis-based products including tetrahydrocannabinol (THC), the psychoactive component of cannabis (marijuana) [ 18 ].…”
Section: Resultsmentioning
confidence: 99%
“…Our participants were younger and more ethnically diverse, and 90% were adolescents. A Swedish study of 2185 teenagers found reported e‐cigarette use was associated with personal and parental tobacco use, physical inactivity and an unhealthy diet 8 . We did not collect data on all these variables.…”
Section: Discussionmentioning
confidence: 99%
“…4 However, there are few UK data on the extent of clustering of risky behaviours, specifically in inner-city, ethnically diverse adolescents 6,7 ; there have been calls for more studies of substance use and sexual behaviour in teenagers. 2,5,8 Adolescence is a key stage in life when unhealthy habits are most often established, 9 and these can lead to health inequalities later in life. 1,10 Using cross-sectional, baseline data from the 'Test and treat' (TnT) feasibility trial (which explored the uptake of rapid chlamydia tests and same-day on-site treatment 11 ), we examined the prevalence of reported alcohol use, smoking (including heavy smoking defined as ≥10 cigarettes daily) and vaping, and explored possible associations with numbers of sexual partners (≥2 versus 0-1) within the past year.…”
Section: Backg Rou N Dmentioning
confidence: 99%
See 1 more Smart Citation